Diagnostic value of macular blood flow in normal tension glaucoma - A.Sh. Zagidullina; V.U. Galimova; A.I. Arslanova; A.R. Nugmanova (РМЖ "Клиническая офтальмология")
A.Sh. Zagidullina1, V.U. Galimova1, A.I. Arslanova1,2, A.R. Nugmanova1 1Bashkir State Medical University, Ufa, Russian Federation 2City Clinical Hospital No. 8, Ufa, Russian Federation Aim: to evaluate macular microcirculation in patients with early newly diagnosed normal tension glaucoma (NTG) and primary open-angle glaucoma (POAG) with elevated IOP using optical coherence tomography angiography (OCTA). Patients and Methods: patients aged 45–65 years with early newly diagnosed NTG (35 patients, 35 eyes) or POAG with elevated IOP (43 patients, 43 eyes) and healthy individuals without ocular disorders (n=50) were examined. All patients underwent OCTA by measuring vascular density (VD, %) using the ETDRS grid (central Fovea and Parafovea) and retinal thick-ness using the Angio Retina 3.0 protocol of the Optovue XR Avanti with the AngioVue function (Optovue, USA). Results: in patients with NTG and POAG, a decrease in vascular density in the superficial choroid plexus was detected. In patients with NTG, retinal thickness in the Fovea, Parafovea, Inferior, and Nasal quadrants was lower than that in the control group and correlated with VD in the Fovea and superior Parafovea of the superficial choroid plexus. The severity of focal losses of the retinal ganglion cell complex was lower than that in the control group and demonstrated a significant weak negative correlation (r=-0.487, p<0.01) with the vascular density index in the Fovea of the superficial choroid plexus. In patients with POAG, retinal thickness in the Fovea and Parafovea was also reduced and correlated with vascular density in the temporal and inferior Parafovea. The severity of global losses of the retinal ganglion cell complex demonstrated a weak negative correlation (r=-0.464, p<0.01) with microcirculation density in the Fovea of the superficial retinal choroid plexus. Conclusion: OCTA revealed a decrease in vascular density in the superficial choroid plexus in early glaucoma. Moreover, a significant difference between NTG and POAG in the Fovea and Parafovea was revealed. Our study established the predominance of vascular changes in patients with NTG. OCTA parameters of the superficial choroid plexus identify microcircula-tion abnormalities at early glaucomatous damage. Keywords: primary open-angle glaucoma, normal tension glaucoma, OCT, optical coher-ence tomography angiography, vascular density index. For citation: Zagidullina A.Sh., Galimova V.U., Arslanova A.I., Nugmanova A.R. Diagnostic value of macular blood flow in normal tension glaucoma. Russian Journal of Clinical Ophthalmology. 2023;23(4):174–180 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-1.